2015
DOI: 10.1101/cshperspect.a022699
|View full text |Cite
|
Sign up to set email alerts
|

Immunity and Inflammation in Epilepsy

Abstract: This review reports the available evidence on the activation of the innate and adaptive branches of the immune system and the related inflammatory processes in epileptic disorders and the putative pathogenic role of inflammatory processes developing in the brain, as indicated by evidence from experimental and clinical research. Indeed, there is increasing knowledge supporting a role of specific inflammatory mediators and immune cells in the generation and recurrence of epileptic seizures, as well as in the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
145
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(160 citation statements)
references
References 177 publications
(225 reference statements)
2
145
0
3
Order By: Relevance
“…At this point, genetic testing is available for several single genes, as well as complex genetic disorders (see Coulter and Steinhäuser 2015;Vezzani et al 2015). A basic karyotype can be performed to evaluate for a chromosomal anomaly, especially in a patient with dysmorphic features.…”
Section: Genetic Testingmentioning
confidence: 99%
“…At this point, genetic testing is available for several single genes, as well as complex genetic disorders (see Coulter and Steinhäuser 2015;Vezzani et al 2015). A basic karyotype can be performed to evaluate for a chromosomal anomaly, especially in a patient with dysmorphic features.…”
Section: Genetic Testingmentioning
confidence: 99%
“…Additionally, using chimeric mice and cell ablation techniques, these investigators showed that HCA2 receptors were present on bone marrow-derived monocytes and macrophages that infiltrated the brain, and that the neuroprotective effect of BHB required HCA2 receptor activation on these immune cells, and further, involved prostaglandin synthesis. This study was the first clear demonstration that BHB can exert a profound anti-inflammatory effect, something that has been clearly recognized to reduce seizure activity [60]. …”
Section: Hca2 Receptors and The Nrlp3 Inflammasomementioning
confidence: 99%
“…Recent studies have introduced the neurological sequelae, in which pro-inflammatory cytokines with proictogenic properties (such as IL-1β, high-mobility group box 1 [HMGB1], cyclooxygenase-2 [COX-2], prostaglandin E2 [PGE2], IL-6, TNF-α and nicotinamide adenine dinucleotide phosphate-oxidase [NOX2]) play an important role in seizure generation and exacerbation (Vezzani, Auvin, Ravizza & Aronica 2012, Wu & Huang 2015, Dey, Kang, Qiu, Du & Jiang 2016). IL-1β and HMGB1 induce the proinflammatory innate immunity IL-1 receptor type 1 (IL-1R1)/toll-like receptor 4 (TLR4) signaling (Ravizza, Kostoula & Vezzani 2013, Vezzani, Lang & Aronica 2016) leading to neuroinflammation, its perpetuation and thus modulating seizure susceptibility, lowering seizure threshold and epileptogenesis (Maroso, Balosso, Ravizza, Liu, Aronica, Iyer et al 2010, Riazi, Galic & Pittman 2010, Vitaliti, Pavone, Mahmood, Nunnari & Falsaperla 2014, Vezzani, Lang & Aronica 2016). …”
Section: Inflammation and Neuroinflammation: Definitions Targets mentioning
confidence: 99%